Models for Agricultural Drought Investigations at Koraput (Orissa) - Sudhishri, Susama; Panda, R.K.; Patnaik, U.S. (Journal of Soil and Water Conservation, 2022)
Rainfall and maximum and minimum temperature data of 32 years (1970- 2001) at Semiliguda, Koraput (Orissa) were analysed to study the weekly, monthly and yearly drought and comparing the different models for finding a suitable method for drought investigation by studying the water balance. The IMD method was adjudged more suitable for drought identification than the revised IMD method. Frequency analysis was done to predict weekly, monthly, seasonal and annual rainfall at different per cent chances.